Experimental study of the thermal conductivity of polyurethane foams. (25th March 2017) - Zhang, Hu; Fang, Wen-Zhen; Li, Yue-Ming; Tao, Wen-Quan
Highlights: Thermal conductivity of PU foam is measured under various environments by TPS method. Spectral extinction coefficient of PU foam is measured by FTIR. Thermal conductivity of PU foam increases non-monotonically with temperature. Thermal conductivity of PU foam increases as high as 10–18% in moist air. Radiative thermal conductivity of PU foam can be calculated by Rosseland model. Abstract: Polyurethane foams are widely used in energy conservation field and thermal conductivity is one of the most important properties. To reveal and optimize the thermal insulation performance of PU foams, the thermal conductivity of five PU foam samples formed by blowing agents of CP, CP + IP, CP + 245fa and CP + 245fa + LBA are measured using transient plane source method under various environment. Influences of temperature, humidity, water uptake, alternate high and low temperature, long time storage at high temperature and gas pressure of the atmosphere on the thermal conductivity of PU forms are investigated comprehensively. The mechanism of temperature that affects the thermal conductivity of PU foams is discussed. Fourier transform infrared spectroscopy is adopted to measure the spectral extinction coefficients of these five samples. With the spectral extinction coefficient, the radiative thermal conductivity is calculated from Rosseland model. Then the contributions of radiative heat transfer to the effective thermal conductivity are decomposed. The thermal conductivity of five foams increases non-monotonically with temperature. When stored in moist air, thermal conductivity can increase as high as 10–18%. Radiative thermal conductivity contributes 3.6–4.1% at −40 °C, 7.3–9.0% at 20 °C and 9.1–11.8% at 70 °C to the effective thermal conductivity.